2020
DOI: 10.1002/ange.202004841
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Oxygen Reduction to Hydrogen Peroxide Catalyzed by Nickel Single‐Atom Catalysts with Tetradentate N2O2 Coordination in a Three‐Phase Flow Cell

Abstract: Carbon‐supported NiII single‐atom catalysts with a tetradentate Ni‐N2O2 coordination formed by a Schiff base ligand‐mediated pyrolysis strategy are presented. A NiII complex of the Schiff base ligand (R,R)‐(−)‐N,N′‐bis(3,5‐di‐tert‐butylsalicylidene)‐1,2‐cyclohexanediamine was adsorbed onto a carbon black support, followed by pyrolysis of the modified carbon material at 300 °C in Ar. The Ni‐N2O2/C catalyst showed excellent performance for the electrocatalytic reduction of O2 to H2O2 through a two‐electron trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For long-term and continuous production, the flow of electrolyte solutions is essential. [83] A two-compartment device developed into flow type for modular-scale and low-cost H 2 O 2 electrosynthesis was proposed by Chen et al (Figure 7b). [12] T. Pérez et al reported a filter-press flow cell possessing turbulence promoters with efficiency close to 100 % and low energy consumption.…”
Section: Minireviewsmentioning
confidence: 99%
“…For long-term and continuous production, the flow of electrolyte solutions is essential. [83] A two-compartment device developed into flow type for modular-scale and low-cost H 2 O 2 electrosynthesis was proposed by Chen et al (Figure 7b). [12] T. Pérez et al reported a filter-press flow cell possessing turbulence promoters with efficiency close to 100 % and low energy consumption.…”
Section: Minireviewsmentioning
confidence: 99%
“…Similarly, O,N-dual coordinated Ni centers were anchored on carbon black Ni-N 2 O 2 /C, which was fabricated by pyrolyzing Ni-coordinated Jacobsen's ligand (Fig. 11d) [88]. On this material, a Ni-N 2 O 2 coordination sphere similar to the Ni species in the Jacobsen-Ni complex was successfully produced (Fig.…”
Section: Modification Of Neighboring Coordinatingmentioning
confidence: 99%
“…DFT calculations revealed that the weaker adsorption of *OOH on Pt 1 /TiC facilitated the (d-h) are reprinted with permission from Ref. [88]. Copyright © 2020, John Wiley and Sons release of active sites, leading to better catalytic activity and selectivity.…”
Section: Support Coupling Modificationmentioning
confidence: 99%
“…[4] Wang et al [5] have reported that the metal sites in iron-carbon-oxygen (FeÀ CÀ O) motifs decrease the potential to 0.82 V vs. reversible hydrogen electrode (RHE) to deliver 0.1 mA cm À 2 current density with a high H 2 O 2 FE of 95 %. Recently, Zhang et al [6] have reported the carbon supported nickel (Ni) SACs possessing NiN 2 O 2 coordination, showing a H 2 O 2 FE of 91 % at 70 mA cm À 2 current density.…”
mentioning
confidence: 99%
“…Due to this low content of Ni, only two Raman peaks at � 1350 cm À 1 (D band) and � 1600 cm À 1 (G band) are detected (Figure S4), and no obvious peak for Ni 2p is found in X-ray photoelectron spectroscopy (XPS) spectra of N 4 Ni 1 O 2 /OCNTs (Figure 2c and Figure S5). The C 1s of the catalyst can be divided into four carbon species, [6] including CÀ C/C=C, CÀ N, CÀ O, and C=O (Figure S6). And the N 1s can be decomposed to five peaks, [13] And the peak centered at 532.4 eV could be assigned to Nibonded O.…”
mentioning
confidence: 99%